Point-of-Care Diabetes Diagnostics: Towards a Self-Powered Sensor - Inês Vinagre; Gabriela V. Martins; Joaquim A. Alves; Felismina T.C. Moreira (Micromachines)
A cutting-edge biosensor has been developed to monitor blood glucose levels, which is particularly vital for people with diabetes. This advanced technology uses a miniaturized and membraneless enzymatic fuel cell (EFC) as a compact electrical reader for rapid on-site diabetes diagnosis. Using disposable screen-printed gold electrodes (Au-SPE) modified with the enzyme glucose oxidase (GOx), the biosensor enables the oxidation of glucose at both the anode (counter electrode) and cathode (working electrode) of the EFC. The cathode contains graphene oxide/Prussian blue nanocubes (GO/PBNCs), while the anode uses a biographene layer. Both electrodes were modified with GOx by electrostatic/hydrogen bonding the enzyme to the modified electrodes surface. Individual evaluations of each electrode system emphasized their effectiveness. The integration of both electrodes resulted in an EFC that can generate an output power of approximately 1.8 μW/cm2 at a glucose concentration of 5 mmol/L, which is very close to physiological conditions (3.8 to 6.9 mmol/L). This technology represents a significant advance and promises fully autonomous diagnostic devices suitable for a wide range of analytes. It paves the way for diagnostics everywhere and marks a fundamental shift in point-of-care (PoC) diagnostics.